Presence of Group A streptococcus frequently assayed virulence genes in invasive disease: a systematic review and meta-analysis - Rampersadh, Kimona; Salie, M. Taariq; Engel, Kelin C.; Moodley, Clinton; Zühlke, Liesl J.; Engel, Mark E. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction It is currently unclear what the role of Group A streptococcus (GAS) virulence factors (VFs) is in contributing to the invasive potential of GAS. This work investigated the evidence for the association of GAS VFs with invasive disease. Methods We employed a broad search strategy for studies reporting the presence of GAS VFs in invasive and non-invasive GAS disease. Data were independently extracted by two reviewers, quality assessed, and meta-analyzed using Stata®. Results A total of 32 studies reported on 45 putative virulence factors [invasive (n = 3,236); non-invasive (n = 5,218)], characterized by polymerase chain reaction (PCR) (n = 30) and whole-genome sequencing (WGS) (n = 2). The risk of bias was rated as low and moderate, in 23 and 9 studies, respectively. Meta-,analyses of high-quality studies (n = 23) revealed a significant association of speM [OR, 1.64 (95%CI, 1.06; 2.52)] with invasive infection. Meta-analysis of WGS studies demonstrated a significant association of hasA [OR, 1.91 (95%CI, 1.36; 2.67)] and speG [OR, 2.83 (95%CI, 1.63; 4.92)] with invasive GAS (iGAS). Meta-analysis of PCR studies indicated a significant association of speA [OR, 1.59 (95%CI, 1.10; 2.30)] and speK [OR, 2.95 (95%CI, 1.81; 4.80)] with invasive infection. A significant inverse association was observed between prtf1 [OR, 0.42 (95%CI, 0.20; 0.87)] and invasive infection. Conclusion This systematic review and genomic meta-analysis provides evidence of a statistically significant association with invasive infection for the hasA gene, while smeZ, ssa, pnga3, sda1, sic, and NaDase show statistically significantly inverse associations with invasive infection. SpeA, speK, and speG are associated with GAS virulence; however, it is unclear if they are markers of invasive infection. This work could possibly aid in developing preventative strategies.